Isolation and characterization of styryllactone of Goniothalamus ridleyi - Samsiah Jusoh,; Zuriati Zakaria,; Fasihuddin Ahmad,; Laily Din, (Universiti Kebangsaan Malaysia, 2015)
Phytochemical studies were conducted on the stem bark, stem, root and fruit of Goniothalamus ridleyi (Annonaceae) collected at Post Brooke, Gua Musang, Kelantan, Malaysia. Extraction using organic solvent followed by extensive purification using standard procedure afforded an epoxystyryllactone, 5-acetoxyisogoniothalamin oxide (1) from the stem bark and fruit; a styryllactone, 5-acetoxygoniothalamin (2) and a styrylpyrone, dehydrogoniothalamin (3) from the stem and root; a styryllactone, 5-hydroxygoniothalamin (4) from the root and styrylpyrone as well as goniothalamin (5) from the fruit. These compounds were characterized using spectroscopic techniques.